Dispassionate reporting? the construction of the Zimbabwe men’s cricket team in the Herald and Dailynews. - Mukwekwerere, Pardon (Midlands State University, 2017)
The study seeks to assess how the Zimbabwe men’s cricket team is constructed by the two mainstream newspapers, The Herald and DailyNews. Making of or construction of reality is within the daily interactions of human in society. Society helps in shaping people’s view of the world. Construction means making-up or “creating reality”. The Herald and DailyNews articles between January 2016 and November 2016 constructed the Zimbabwe men’s cricket team as failures and how it makes headlines in the print media specifically in The Herald and DailyNews. The researcher sought to find the effectiveness of The Herald and DailyNews in constructing the cricket team and players, and why they make headlines in the newspapers. The study was informed by the following theoretical framework namely framing theory and political economy of the media. In addition, the research made use of qualitative research methods, critical discourse analysis and content analysis. Since the study has to be understood under its contextual meanings to find out how and why the two newspapers constructed the Zimbabwe men’s cricket team as the worst team in the game of cricket, and however a little bit of quantitative research methods were used. The findings of the study revealed that the political, economic and community identity issues traverse ion the management and production of sports news in The Herald and DailyNews bringing out a parasitism relationship between the two disciplines, sport and the mass media.